Good Corporate Governance and Corporate Social Responsibility in Moderating the Effect of Environmental Performance on Financial Performance - Koko Safitri (Publisher Cv. Inara, 2021)
The purpose of this study was to determine how much influence environmental performance has on financial performance and the influence of Good Corporate Governance and Corporate Social Responsibility on companies listed on IDX30 for the period February – April 2021. By using a descriptive approach and the SEM-PLS method. This research was conducted by taking secondary data. Sources of data were obtained from the annual report published on the Indonesia Stock Exchange (IDX) in 2019 on the website (www.idx.co.id) and the CPRP report issued by the Ministry of Environment and Forestry in 2018-2019. The results showed that; (1) Environmental performance has an effect on financial performance, with P Values of 0.023 <0.05. (2) Good Corporate Governance does not moderate the relationship between environmental performance and financial performance, with P Values of 0.196 > 0.05. (3) Corporate Social Responsibility as a moderator of the relationship between environmental performance and financial performance, with P Values of 0.024 <0.05.